Production of biodiesel form Jatropha curcas seed oil - Abdelrahman, Maha A. A; Yassin, Atif A. A.; Hussein, Ismail Hassan; Mirghani, Mohamed Elwathig Saeed; Karama, Abdallah (University of Gezira, 2017)
This study was carried out to produce biodiesel from freshly harvested Jatropha curcus (J. curcus) seed oil. J. curcus seeds has high oil content (40%), the free fatty acids ranged between 1.6 - 1.75 %, peroxide value was 2.6 meq/kg, moisture content in crude oil was (0.2 -0.3%) and the saponificatio value was ranged between 185 t0 189 mg KOH/g oil. The main fatty acids were oleic 39.60% and linoleic 34.64%. Unsaturated fatty acids were 75.54%wt, while saturated fatty acids were 24.46% wt. The specifications of biodiesel produced were; density is reduced from 0.9198 to 0.8810 g/cm3. The kinematic viscosity at 40o C was reduced from 36.37 to 4.809 mm2/s, and the flash point was 187oC. Biodiesel produced complies with the requirement of the American Society for Testing and m,aterials (ASTM) standard D6751-09, and the Committee of Standardization in Europe (CEN) standard EN 14214 specifications.